The Effects of Liquidity Regulation on Bank Assets and Liabilities - Patty Duijm; Peter Wierts (Tinbergen Institute, 2014)
Under Basel III rules, banks become subject to a liquidity coverage ratio (LCR) from 2015 onwards, to promote short-term resilience. We investigate the effects of such liquidity regulation on bank liquid assets and liabilities. Results indicate co-integration of liquid assets and liabilities, to maintain a minimum short-term liquidity buffer. Still, microprudential regulation has not prevented an aggregate liquidity cycle characterised by a pro-cyclical pattern in the size of balance sheets and risk taking. Our error correction regressions indicate that adjustment in the liquidity ratio is balanced towards the liability side, especially when the liquidity ratio is below its long-term equilibrium. This finding contrasts established wisdom that the LCR is mainly driven by changes in liquid assets. Policy implications focus on the need to complement microprudential regulation with a macroprudential approach. This involves monitoring of aggregate liquid assets and liabilities and addressing pro-cyclical behaviour by restricting leverage.
Keywords: E44; G21; G28; 330; market liquidity; funding liquidity; liquidity regulation; liquidity coverage ratio; Basel III; banks; microprudential; macroprudential; co-integration; error correction models